Inconsistencies in the Reality of Employment Law in Indonesia in International Legal Conventions - Mofea, Sukhebi (Journal of Ecohumanism, 2024)
The problem in this article is that there are inconsistencies and gaps between national and international labor regulations, many provisions in national labor laws are not in accordance with international standards that have been ratified by Indonesia, such as provisions regarding minimum wages, severance pay, outsourcing and protection for migrant workers. This type of research is qualitative research using normative legal research methods which use data collection techniques using literature study. The purpose of this research is to discuss and examine inconsistencies or conflicts between labor laws that occur in Indonesia and international legal convention regulations that regulate labor law. The results of the research and discussion are that regulations regarding freedom of association for workers in Indonesia began with the ratification of ILO Convention No. 87 Concerning Freedom of Association and Protection of the Right to Organize and ILO Convention No. 98 Concerning the Implementation of the Principles of the Right to Organize and Collective Bargaining.